Examination of memory and culture based on the architectural facade: Facadism at Beyoğlu district - Aliye Rahsan Karabetca; Sedef Sav (Anuari d’Arquitectura i Societat)
İstanbul owns a historical texture rich in architecture, culture, and memory, which are seen in very few metropolises. This city, which has undergone many changes due to social, political, and cultural reasons, has begun to lose its many important values day by day. The biggest reason for this is that the city is culturally vibrant, so that it is desired to be transformed into a source of political income. However, solutions that will strengthen the current situation of İstanbul as a whole and ensure its continuation on solid foundations should be determined and implemented. In this study, Beyoğlu district is considered as the pilot area, one of the rare regions that this wealth has survived to the present day. The first aim of this study is to determine the reasons and purposes for the unnecessary reconstructions of historical buildings located in Beyoğlu, far from their original look, so-called facadism. The second aim of this study is to identify the changes made on the facades in terms of culture and memory and propose suggestions by using photographing, literature review, and analysis with collage methods. In the study, three of the selected four buildings are located on İstiklal street, the other one on Sıraselviler street, two places where the rapid structural/architectural identity transformation in the last 15-20 years can be seen most clearly. As a result of this study, it has been determined that the functions of historical buildings are being degenerated. Their facades are only kept as masks, and the architectural memory is devolved in this way.